Large‐Area Lead Monolayers under Cover: Intercalation, Doping, and Phase Transformation - Franziska Schölzel; Peter Richter; Andres David Peña Unigarro; Susanne Wolff; Holger Schwarz; Adrian Schütze; Niels Rösch; Sibylle Gemming; Thomas Seyller; Philip Schädlich (Small Structures, 2025)
Intercalation is a promising approach for tailoring the electronic structure of epitaxial graphene on SiC. It enables the formation of otherwise unstable 2D phases of elements and allows the investigation of the interplay between the 2D materials and the substrate. Detailed studies have been conducted on the Pb intercalation process, as well as the structure and electronic properties of the 2D Pb layer using low‐energy electron microscopy and photoelectron spectroscopy. The low‐energy bands of Pb show good agreement with density‐functional theory calculations. A uniform Pb intercalation layer with (1 × 1) periodicity with respect to the SiC substrate is found. The quasifreestanding graphene is effectively screened from the doping influence of the substrate, leading to charge neutrality. Instead, the 2D Pb layer compensates for the spontaneous polarization of the substrate, allowing for the doping of a metal layer under cover. A phase transformation from the (1 × 1) intercalation phase into a bubble phase with quasi‐tenfold periodicity with respect to graphene occurs if the system is provided with sufficient energy. These results experimentally quantify the interaction between the 2D Pb layer, the substrate, and the graphene layer, demonstrating a first step toward controlling the diversity of 2D Pb phases.